Contrarian Majority Rule Model with External Oscillating Propaganda and Individual Inertias - Gimenez, Maria Cecilia (2023)
We study the Galam majority rule dynamics with contrarian behavior and an oscillating external propaganda in a population of agents that can adopt one of two possible opinions. In an iteration step, a random agent interacts with three other random agents and takes the majority opinion among the agents with probability (Formula presented.) (majority behavior) or the opposite opinion with probability (Formula presented.) (contrarian behavior). The probability of following the majority rule (Formula presented.) varies with the temperature T and is coupled to a time-dependent oscillating field that mimics a mass media propaganda, in a way that agents are more likely to adopt the majority opinion when it is aligned with the sign of the field. We investigate the dynamics of this model on a complete graph and find various regimes as T is varied. A transition temperature (Formula presented.) separates a bimodal oscillatory regime for (Formula presented.), where the population’s mean opinion m oscillates around a positive or a negative value from a unimodal oscillatory regime for (Formula presented.) in which m oscillates around zero. These regimes are characterized by the distribution of residence times that exhibit a unique peak for a resonance temperature (Formula presented.), where the response of the system is maximum. An insight into these results is given by a mean-field approach, which also shows that (Formula presented.) and (Formula presented.) are closely related.